Rekonstruksi Pendidikan Akidah dan Akhlak Islami sebagai Respon terhadap Degradasi Moral Mahasiswa di Era Globalisasi - Adisti Anggraini; Nur Hidayat (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2025)
The ethical deterioration among university students in the globalization era has emerged as a significant concern, evidenced by diminishing academic integrity, departures from social standards, and the waning internalization of Islamic principles. This situation indicates that moral education by itself is inadequate unless it is based on a solid foundation of Islamic belief (aqidah). This research seeks to rebuild the conceptual foundation of Islamic aqidah and ethical education as a reaction to the decline in students' morality within the context of globalization. The study utilizes a qualitative descriptive library research approach by thoroughly examining books, both national and international journal articles, and other pertinent academic resources. The results indicate that the revitalization of Islamic aqidah and ethical education should be holistic and context-specific, establishing aqidah as the knowledge-based foundation for character development and akhlaq as its practical expression in everyday life. The incorporation of Islamic moral principles into the Merdeka Curriculum and campus environment is suggested as a strategic approach to cultivate devoted, ethical, moderate, and high-integrity university students to meet global challenges.